The Influence of Work Motivation, Spiritual Intelligence, and Work Environment on Teacher Performance with Job Satisfaction as an Intervening Variable - Lilis Yunia Wulandari; Trias Setyowati; Abadi Sanosra (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The purpose of this study is to examine and analyze the effet of work motivation, spiritual intelligence, and work environment on teacher performance at SMPN 2 Ambulu Jember both directly and indirectly with job satisfaction as an intervening variable. Method: This study is an explanatory research with a quantitative approach. The population in this study were all 73 teachers at SMPN 2 Ambulu Jember and the sampling technique used the census method. Data analysis used path analysis using the SEM (Structural Equation Modeling) model with the Warp PLS 5.0 program. Results:  The results shown that work motivation, spiritual intelligence, and work environment significantly effect on job satisfaction. Work motivation and work environment insignificant effect on teacher performance, while spiritual intelligence has significant effect on teacher performance. Job satisfaction has significant effect on teacher performance. Work motivation and work environment significant effect on teacher performance, with job satisfaction as an intervening variable. Spiritual intelligence insignificant effect on teacher performance, with job satisfaction as an intervening variable. Novelty: This study offers novelty by integrating the variables of work motivation, spiritual intelligence, and work environment in one comprehensive model to explain teacher performance through the mediating role of job satisfaction.